2021
DOI: 10.1021/acs.nanolett.0c05148
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Engineering of Clusterzyme for Relieving Acute Neuroinflammation through Lattice Expansion

Abstract: Natural enzymes are efficient and versatile biocatalysts but suffer in their environmental tolerance and catalytic stability. As artificial enzymes, nanozymes can improve the catalytic stability, but it is still a challenge to achieve high catalytic activity. Here, we employed atomic engineering to build the artificial enzyme named Au24Ag1 clusterzyme that hosts an ultrahigh catalytic activity as well as strong physiological stability via atom manipulation. The designed Au24Ag1 clusterzyme activates the Ag–S a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 78 publications
0
50
0
Order By: Relevance
“…240 Recent studies have shown that the atomic-level Au 24 Ag 1 cluster enzyme has ultra-high physiological stability and its unique CAT and GPxlike enzyme activities can effectively inhibit inflammatory molecules in the brain, which is expected to play an essential role in nanomedicine. 241 On the other side, antibacterial is an essential property of nanozymes. Ultra-small size (<2 nm) Au NPs have been found to interact with bacteria and destroy their cell membrane.…”
Section: Nanozymementioning
confidence: 99%
“…240 Recent studies have shown that the atomic-level Au 24 Ag 1 cluster enzyme has ultra-high physiological stability and its unique CAT and GPxlike enzyme activities can effectively inhibit inflammatory molecules in the brain, which is expected to play an essential role in nanomedicine. 241 On the other side, antibacterial is an essential property of nanozymes. Ultra-small size (<2 nm) Au NPs have been found to interact with bacteria and destroy their cell membrane.…”
Section: Nanozymementioning
confidence: 99%
“…Unlike traditional nanozyme, bioactive gold clusters exhibit the high efficient renal clearance and negligible toxicity even at very high injected dose (500 mg/kg) [24,25,27]. Moreover, due to ultrasmall size, the gold clusters can enter cell or injury site easily, resulting in high efficient treatment [26,28]. Gold clusters possess activities like SOD, CAT and GPx enzymes, performing significant antioxidant effects in TBI treatment [26,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to ultrasmall size, the gold clusters can enter cell or injury site easily, resulting in high efficient treatment [26,28]. Gold clusters possess activities like SOD, CAT and GPx enzymes, performing significant antioxidant effects in TBI treatment [26,[28][29][30][31]. Though nanotechnologies for TBI diagnosis and monitoring were employed to promote the activity and utilization of nanozymatic biocatalysts like atom engineering, surface modification, and size modulation [32][33][34], it remains painless and chanllenged for clinical translation [12,15,[29][30][31][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the ceria nanozymes exhibited enzymatic activities like SOD and CAT on scavenging RONS via redox cycle between Ce 4+ and Ce 3+ [12,18,25,28]. Gold nanoclusters can simulate SOD, CAT and GPx enzymes displaying compelling effects in TBI treatment with superb antioxidant capacities [29][30][31][32][33]. Besides, diagnosis and monitoring methods based on nanotechnologies especially activable nanoprobes are being developed for TBI [34][35][36], and technologies like atom engineering, surface modi cation, and size modulation were employed to promote the activity and utilization of nanozymatic biocatalysts [30][31][32][37][38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the TBI group, all nanoclusters promoted the healing progress among which the Au 24 Cd 1 presented the best healing effect followed by Au 24 Cu 1 , demonstrating the therapeutic effect of the nanoclusters especially the Au 24 Cd 1 and Au 24 Cu 1 . In addition, we evaluated the oxidative stress-related indicators, including SOD, GSH/GSSG, MDA, and H 2 O 2 in TBI mice after nanoclusters treatment[33,57].TBI can consume lots of SOD and GSH, leading to the decrease of SOD and GSH activity and the increase of MDA and H 2 O 2 amount (Fig.5c-f). The presence of over-excessive MDA H 2 O 2 and GSSG indicates severe oxidative stress in TBI mice.…”
mentioning
confidence: 99%